Sociolinguistic and Linguocultural Features of English-Language Matrimonial Advertisements - Tsymbaliuk, Viktoriia (Studia Philologica, 2024)
The article examines the linguistic features of English-language matrimonial advertisements in the context of sociolinguistic and linguocultural factors that influence their construction and subsequent distribution on Internet sites and dating apps. The popular dating apps Tinder and Badoo were chosen for the analysis. The diversity in the content of matrimonial advertisements, the views of candidates on marriage, their expectations of the other person, and the ways they present themselves reflects the rapid and dramatic transformations taking place in the social and cultural life of society. The paper explores the lexical composition, stylistic features and communication strategies used by the authors of matrimonial advertisements to represent themselves and their desires, as well as to express their expectations of a potential partner. Virtual dating platforms, such as websites and apps, provide users with the opportunity to consciously shape and manage their image. This is especially important in the context of the analysed matrimonial advertisements, where language becomes a tool for creating the desired impression and communication is defined as strategic. The importance of effective communication is to ensure that the message is properly received and the information conveyed is accurately understood. Communicative interaction in the context of matrimonial advertisements contributes to building the desired relationship for the authors of matrimonial advertisements. The authors of English-language matrimonial advertisements seek to achieve the goal of communication, which is to find a person who can become a romantic partner and perform other roles in the life of the ad’s subject. The article explores the sociolinguistic and linguocultural features of this phenomenon, with a focus on how linguistic devices contribute to the impression management in the digital space.